End-diastolic forward flow in repaired tetralogy of Fallot: Mid-term outcomes from a single center - Huang, Ying; Cai, Xiaowei; Zhong, Lishan; Xie, Wen; Lou, Qi; Ma, Jianrui; Chen, Jimei; Zhuang, Jian; Wen, Shusheng; Zhao, Junfei (Frontiers in Cardiovascular Medicine, 2023)
Background: Pulmonary arterial end-diastolic forward flow (EDFF) following repaired tetralogy of Fallot (rTOF) is recognized as right ventricular (RV) restrictive physiology, which is closely related to poor prognosis. This study sought to review mid-term experience and investigate the risk factors of EDFF in the rTOF patients. Methods: From September 2016 to January 2019, 100 patients (age < 18 years old) who underwent complete tetralogy of Fallot (TOF) repair were enrolled and were divided into EDFF group (n=52) and non-EDFF group (n=48) based on the presence of postoperative EDFF. Elastic net analysis was performed for variable selection. Univariate and multivariate logistic analyses were used to analyze the correlation between risk factors and EDFF. Results: EDFF group had lower systolic blood pressure (P=0.037), diastolic blood pressure (P=0.027), and higher vasoactive-inotrope score within 24 hours after surgery (P=0.022) than non-EDFF group. Transannular patch (TAP) was an independent predictor of postoperative EDFF [P=0.029, OR: 2.585 (1.102~6.061)]. Patients were followed up for a median of 2.6 years [interquartile range (IQR) 1.6] after the first TOF repair. During follow-up, the prevalence of the EDFF was lower in those with pulmonary valve (PV) reconstructions than that in those undergoing patch enlargement without PV reconstructions in the primary TOF repair (P<0.001). Conclusions: EDFF was associated with TAP. Patients with EDFF might have a transient hemodynamic instability in the early postoperative period. PV reconstructions in the TOF repair might reduce the incidence of EDFF in the mid-term follow-up.